The value of the World Conferences on Research Integrity: perspectives from Peru - Dejo Vásquez, Mariela (2021)
“The World Conferences on Research Integrity (WCRIs), six to date, were initiated at a time when researchers in various countries were at quite different stages in their thinking about research integrity. Over the course of the past decade, the global conferences have reflected and documented significant changes in the way research integrity is viewed and supported”